Selecting patients with sickle cell disease for gene addition or gene editing‐based therapeutic approaches: Report on behalf of a joint EHA Specialized Working Group and EBMT Hemoglobinopathies Working Party consensus conference - Lucia de Franceschi; Franco Locatelli; David Rees; Christian Chabannon; Jean‐Hugues Dalle; Stefano Rivella; Achille Iolascon; Stephan Lobitz; Miguel R. Abboud; Josu de la Fuente; Pagona Flevari; Emanuele Angelucci; et al. (HemaSphere)
ABSTRACT Sickle cell disease (SCD) remains associated with reduced life expectancy and poor quality of life despite improvements observed in the last decades mostly related to comprehensive care, use of hydroxycarbamide, screening to identify patients at risk of strokes, and implementation of safe transfusion protocols. The course of the disease is highly variable, making it difficult to predict severity and response to therapy. Allogeneic hematopoietic stem cell transplantation potentially provides a cure with a relatively low rate of complications, but few patients have an HLA‐identical sibling. The hopes of patients and healthcare providers have been raised after the initial excellent results of gene therapy studies. However, there is a strong contrast between the high expectations of families and patients and the limited availability of the product, which is technically complex and very expensive. In light of this consideration and of the limited data available on the long‐term efficacy and toxicity of different gene therapy approaches, the European Hematology Association Red Cell & Iron Specialized Working Group (EHA SWG) and the hemoglobinopathy working part of the European Blood & Marrow Transplant (EBMT) Group have prioritized the development of recommendations for selection of patients with SCD who are good candidates for gene therapy. The decision‐making algorithm was developed by a panel of experts in hemoglobinopathies and/or transplantation chosen by EHA SWG and EBMT, to discuss the selection of SCD patients for gene therapy and draw notes on the related clinical problems.